Silicon photonic integration in telecommunications - Doerr, Christopher R. (Frontiers in Physics, 2015)
Silicon photonics is the guiding of light in a planar arrangement of silicon-based materials to perform various functions. We focus here on the use of silicon photonics to create transmitters and receivers for fiber-optic telecommunications. As the need to squeeze more transmission into a given bandwidth, a given footprint, and a given cost increases, silicon photonics makes more and more economic sense.